Low-power operating aluminum nitride nanowire-film ultraviolet photodetector - TEKER, KAŞİF (My University, 2022)
© 2022 Trans Tech Publications Ltd, Switzerland.This work presents the fabrication and testing of a cost-effective, low power consuming, high sensitivity aluminum nitride nanowire-film-based ultraviolet photodetector. Time-dependent dynamics of photocurrent rise and decay have been investigated with varying applied bias ranging from 1 V to 20 V by periodical exposures to 254 nm ultraviolet light. The device shows stable and repeatable photocurrent cycles at a low bias voltage of 1 V indicating the sensitivity and low power operating capability. Furthermore, the photocurrent increases as the bias voltage increases such that the photocurrent at 20 V is approximately seventeen times larger than that of at 1 V. Despite the relatively long device channel length, the device reveals a quick response with a rise time of 270 ms. Moreover, the responsivity of the photodetector has been determined as 3.78 mA/W and 0.201 mA/W at 20 V and 1 V, respectively. This study demonstrates the potential of aluminum nitride nanowires for applications in next generation, low power consumption nanoscale optoelectronic devices in advanced communication, flame detection, air purification, ozone sensing, leak detection and other space monitoring.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Genel Malzeme Bilimi; Fizik Bilimleri; Genel Fizik ve Astronomi; General Materials Science; Physical Sciences; General Physics and Astronomy; Aluminum nitride nanowires; Cost-effective ultraviolet sensors; Low-power operation; Nanowire photodetectors